Respuesta :
Add those equations together
1. 4x = 16, x = 4
2. Multiple the second one by 2
2x+4y=22
4x-4y=-16
6x = 6, x = 1
3. Add them together
8x = 24, x = 3
1. 4x = 16, x = 4
2. Multiple the second one by 2
2x+4y=22
4x-4y=-16
6x = 6, x = 1
3. Add them together
8x = 24, x = 3
In 2, we are asked to solve the systems of equations to solve for the variables using elimination.
3x + 3y = 27-3(x - 3y = -11) 12 y = 60 y = 5 x = 4
2x + 4y = 22 2x - 2y = -8 6y = 30 y = 5 x = 1
5x - y = 0 3x + y = 24 8x = 24 x = 3 y = 15
3x + 3y = 27-3(x - 3y = -11) 12 y = 60 y = 5 x = 4
2x + 4y = 22 2x - 2y = -8 6y = 30 y = 5 x = 1
5x - y = 0 3x + y = 24 8x = 24 x = 3 y = 15